Obstetric and Neonatal Outcomes of Pregnancies with Mild Gestational Hyperglycemia Diagnosed at Gestational Diabetes Mellitus Screening - Akgol, Sedat; Budak, Mehmet Sukru (Gynecology Obstetrics & Reproductive Medicine, 2019)
Objective: The aim of this study was to evaluate obstetric and neonatal outcomes of pregnancies with mild gestational hyperglycemia diagnosed at gestational diabetes mellitus screening. Study design: Between September 2016 and August 2017, the pregnant women diagnosed as normal glycaemia or mild gestational hyperglycemia according to the results of gestational diabetes mellitus screening with 50 g oral glucose challenge test, and 100 g oral glucose tolerance test were compared [Normal glycaemia: Blood glucose value <140 mg/dL 1 hour after 50 g oral glucose challenge test]. Results: The following results were obtained in the normal glycaemia and mild gestational hyperglycemia groups respectively: Mean gestational age at birth, 38.9±1.6 and 39±1.9 weeks; preterm, term, post-term birth rates, 6%, 86.2% 7.8% and 6.8%, 86.4% and 6.8%; cesarean delivery rate, 30.9% and 34.9%; birth weight 3227.9±394.9 and 3241.05±418.5 g; small for gestational age, 4.4% and 2.3%; large for gestational age 4.6% and 7%; without any significant difference between the groups. Five minute APGAR scores were significantly lower in the mild gestational hyperglycemia group compared to the normal glycaemia group. Conclusion: There was no significant increase in adverse pregnancy outcomes such as preterm birth, post-term birth, increased caesarean delivery rate, small for gestational age and large for gestational age, except for a significant decrease in 5 minute APGAR scores in the mild gestational hyperglycemia group compared to the normal glycaemia group in our study.